2020
DOI: 10.21511/ppm.18(4).2020.09
|View full text |Cite
|
Sign up to set email alerts
|

Key elements of local government transparency in new public governance

Abstract: Transparency is a challenge for public administration reforms for now and beyond towards modern and better governance. The economic crisis that occurred has led to a large erosion of public confidence in the effectiveness of government financial management. This study aims to analyze the key elements of local government transparency in new public governance. The research data was obtained through financial reports on local government websites. The sample selection technique used purposive judgment sampling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
4
0
6
Order By: Relevance
“…Nogueira & Jorge (2017) argues that the existence of audit opinion that comes from internal controls makes financial statements more useful for public managers and politicians. Adi & Gusti (2020) showed that audit opinions do not significantly affect elements of local government transparency. Nor et al (2019) evidenced a positive impact of audit opinion on the publication of Indonesian financial statements on websites.…”
Section: Disclosure and Auditmentioning
confidence: 98%
“…Nogueira & Jorge (2017) argues that the existence of audit opinion that comes from internal controls makes financial statements more useful for public managers and politicians. Adi & Gusti (2020) showed that audit opinions do not significantly affect elements of local government transparency. Nor et al (2019) evidenced a positive impact of audit opinion on the publication of Indonesian financial statements on websites.…”
Section: Disclosure and Auditmentioning
confidence: 98%
“…(4) Pengendalian Keuangan, kinerja SIPKD yang baik juga dapat membantu pemerintah daerah dalam mengendalikan keuangan daerah dengan lebih baik, termasuk mengidentifikasi potensi penyalahgunaan dana atau penyelewengan (Hasan, Setiawan, & Cahyono, 2022;Hermawansyah, Aditya, & Susi, 2022). ( 5) Kemampuan Perencanaan, meliputi perencanaan, alokasi pendanaan untuk program pemerintah dan masyarakat, kegiatan monitoring dan evaluasi keuangan yang akurat dan terkini terinformasikan kepada shareholder maupun stockholder Wulandari, Nugroho, & Ambarriani, 2017;Yuniarta & Purnamawati2, 2020).…”
Section: Pendahuluanunclassified
“…Accounting is still related with profit organization/company accounting. Meanwhile, many studies of public accountability lead to government accountability (Setiawan et al, 2021) (Yuniarta & Purnamawati, 2020b). Accountability is an important issue in scientific studies and public administration practices.…”
Section: Introductionmentioning
confidence: 99%